An optimal design for patient‐specific templates for pedicle spine screws placement. Issue 3 (15th May 2012) - Ferrari, V.; Parchi, P.; Condino, S.; Carbone, M.; Baluganti, A.; Ferrari, M.; Mosca, F.; Lisanti, M.
Abstract Background Currently, pedicle screws are positioned using a free‐hand technique or under fluoroscopic guidance, with error in the range 10–40%, depending on the skill of the surgeon. Methods After spine CT acquisition, each vertebra is segmented and the surgeon plans screw positioning in a virtual environment, then the template is designed around the chosen trajectories. This design is based on surgical and mechanical considerations to obtain an optimal solution to guarantee template stability, simple positioning and minimized intervention invasiveness. In vitro evaluation on synthetic spine models and ex vivo animal tests on porcine specimens were performed, with the insertion of 28 Kirschner wires. Results During the in vitro tests, all the surgeons rendered positive evaluations regarding the device and considered template placement to be easy. Ex vivo tests were evaluated by CT examination, which showed that 96.5% of the Kirschner wires had been correctly inserted. Conclusions The proposed solution is a promising, simple, highly precise, low‐cost solution to safely performing posterior stabilization. Such a solution would be of interest even in hospitals in which a few spine interventions are performed per year, and for which it is not reasonable to purchase the equipment required for robotic or navigated approaches. Copyright © 2012 John Wiley & Sons, Ltd.